Educational Potential of Fedir (Theodore) Dudko’s Historical Prose (Based on the Story “Strybozha Granddaughter”) in the Formation of Person’s Value Intentions - Khomyshyn , Olga (Journal of Vasyl Stefanyk Precarpathian National University, 2018)
The great role of the historical fiction in the process of upbringing and exactly in the system of person`s values and intentions that lay the foundations of spirituality, national dignity and vital competence is analyzed in the article. Fedir Dudko’s artistic interpretation of the historical time and the image of a historical character in the projection on the writer’s present time are highlighted as well. The main emphases are made on the educational potential of his prose and persuasiveness of artistic historicism of the story “Strybozha granddaughter” and the determination of the stylistic leitmotif by the statesmanship idea of the work